Investigation of the Performance of Bio-Oils from Three Different Agricultural Wastes as Rejuvenators for Recycled Asphalt - Yalcin, Beyza Furtana; Yilmaz, Mehmet (Turkish Chamber Civil Engineers, 2024)
The aim of this study was to investigate the possibility of using bio-oil obtained from pinecones, olive mill pomace, and wheat straw as rejuvenators for the reuse of aged asphalt binders. Additionally, the biomass used for bio-oil production was selected from waste materials. Therefore, it makes great contributions to both the environment and the economy. B50/70 bitumen was selected as the neat binder. The bio-oils used in the study were obtained as a result of pyrolysis. Bio-oil rejuvenators at 5%, 10% and 20% by the weight of the binder were added to the aged binder obtained from recycled asphalt mixtures to obtain bioregenerated asphalts. The physical and rheological properties of bioregenerated asphalts were investigated and not compared on neat and aged binders through penetration, softening point, rotational viscometer and dynamic shear rheometer tests. In addition, the effects of temperature and biooil content on complex modulus properties were examined using response surface methods. It was found that while the bio-oils increased the penetration values of the aged binders, they also decreased the softening point and viscosity values. The bio-oils significantly modified rutting resistance of the aged binder. The addition of bio-oil improved the viscous components and can rejuvenate the viscoelastic properties of aged asphalt binders to that of almost the original level. In addition, response surface methods results showed that the interactions between both independent variables were effective. Finally, high coefficient of determination (R2) values indicated good agreement between the actual and predicted values. It was recommended as a result of the study that 20% concentration of bio-oil should be used to rejuvenate the aged asphalt binder for reuse in pavement construction.
Keywords: Bio-oil; rejuvenator; aged asphalt; rheological properties; response surface methodology